La publicidad como dispositivo operacional - Caro Almela, Antonio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2009)
The purpose of this paper is to explain how the advertising activity works and the effects derived from it beyond the reductionist perspective of the advertising industry. According to that, this paper aims to expand and increase the theoretical knowledge of advertising. As suggested in Caro (2002-03, 2007), the so called complexity paradigm define the object of science far from the ordinary positivist perspective which analyzes a phenomenon by means of decomposing it in single ingredients. Instead, the complexity paradigm seeks for the «essential principles of organization». Therefore, and according to the complexity that the advertising phenomenon has today, defining how the advertising activity really works and the holistic effects derived from it must be a noteworthy way to give shape to an advertising theory.